2009
DOI: 10.3354/ab00175
|View full text |Cite
|
Sign up to set email alerts
|

Relation of form to life habit in free-living cupuladriid bryozoans

Abstract: Since the late Mesozoic, several bryozoan groups have occupied unstable soft-sediment habitats by adopting a free-living and motile mode of life. Today, the free-living bryozoans often dominate epibenthic faunal communities in these expansive habitats, yet their biology and ecology remain poorly understood. This study examines their unique mode of life by exploring the relationship between form and function in the free-living Cupuladriidae of tropical America. Cupuladriid species occupy distinct niches in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Our behavioural observations are consistent with those made on avicularia of other species, which show a variety of ways in which different forms of avicularia can trap or deter potential predators or settling epibionts and that involve actions of capturing, impaling or sweeping (Kaufmann, 1968(Kaufmann, , 1971Cook & Chimonides, 1978;Chimonides & Cook, 1981;Winston, 1986Winston, , 2010O'Dea, 2009;Carter et al, 2010b). A range of functional needs are considered to be met by different avicularia across Cheilostome lineages (Winston, 1984) and the possibility that avicularia are multifunctional cannot be excluded.…”
Section: Evidence For a Defensive Rolesupporting
confidence: 87%
See 1 more Smart Citation
“…Our behavioural observations are consistent with those made on avicularia of other species, which show a variety of ways in which different forms of avicularia can trap or deter potential predators or settling epibionts and that involve actions of capturing, impaling or sweeping (Kaufmann, 1968(Kaufmann, , 1971Cook & Chimonides, 1978;Chimonides & Cook, 1981;Winston, 1986Winston, , 2010O'Dea, 2009;Carter et al, 2010b). A range of functional needs are considered to be met by different avicularia across Cheilostome lineages (Winston, 1984) and the possibility that avicularia are multifunctional cannot be excluded.…”
Section: Evidence For a Defensive Rolesupporting
confidence: 87%
“…The fact that avicularia are phenotypically variable is well documented (Darwin, 1859(Darwin, , 1872Harmer, 1909;Silén, 1938;Marcus, 1939;Hyman, 1959;Silén, 1977;Winston, 1984Winston, , 1986Winston, , 1991Winston, , 2010 supporting the view that avicularia, as vestigial autozooids, are evolving characters (Lidgard et al, in press). The morphological extremes of the mandible (operculum homologue) displayed by avicularia, from bristle-like mandibles to forms that resemble miniature bird beaks, correlate with functional diversity, where avicularia can function to clean colony surfaces from epibionts (O'Dea, 2009) or sand grains (Cook & Chimonides, 1978;Chimonides & Cook, 1981), or impale and trap passing invertebrates (Kaufmann, 1968(Kaufmann, , 1971Winston, 1984Winston, , 1986Winston, , 1991Winston, , 2010Carter et al, 2010b). Even other clonal invertebrates growing on the colony surface (e.g.…”
Section: Functional Innovation Through Vestigializationmentioning
confidence: 99%
“…In motile, freeliving species, radial symmetry is customary in all but a few Late Cretaceous species, even though all other aspects of morphology and patterns of growth vary greatly amongst species (O'Dea et al, 2008;O'Dea and Jackson, 2009), strongly supporting the idea that radial symmetry is highly adaptive. Indeed, experimental data have shown that deviating from radial symmetry is disadvantageous for motile freeliving species because: (1) asymmetrical colonies are more likely to be turned over by wave action and are less able to move up through sediment passively if they become buried (O'Dea, 2009), implying that radial symmetry confers hydrodynamic stability and better in-faunal coordination; (2) fragments that are always asymmetrical are more prone to burial than circular colonies of the same size (O'Dea, 2009); (3) when a free-living bryozoan is fragmented, initial regenerative growth is always concentrated in the central portions of the sides of the fragments (O'Dea, 2006;O'Dea et al, 2008), thereby ensuring that a circular, more stable shape is rapidly regained by the colony (Håkansson and Thomsen, 2001); (4) initial regenerative growth of asymmetrical fragments is five times more rapid than colony growth at any other time, implying an urgency in the need to create a circular colony (O'Dea, 2006); and (5) fragments that fail to achieve circularity demonstrate higher rates of mortality (O'Dea, 2006(O'Dea, , 2009.…”
Section: Colony Asymmetrymentioning
confidence: 99%
“…They include vibracula which have stiff, whip-like setae that extend above the colony surface and whose functions include: (1) deterring epibiotic organisms from settling on colony surfaces; (2) cleaning fine sediment from the colony surface; and (3) removing or impeding the growth of epibionts (Winston, 1988;Carter et al, 2010). In the free-living bryozoans vibracula also physically lift the colony above the surface of the sea floor (Cook, 1963;Cook and Chimonides, 1978;Winston, 1988;O'Dea, 2009), and can be used to dig colonies out of the sediment if accidentally buried (Håkansson and Winston, 1985).…”
Section: Avicularian Densitymentioning
confidence: 99%
“…Feeding zooids open only on the upper, convex colony surface. Such ‘lunulitiform’ colonies are seldom more than a few centimetres in diameter (Cook & Chimonides, ; Rosso, ; O'Dea, ); they tend to show determinate growth, attaining a maximum size that is characteristic for each particular species. While some populations contain only sexual colonies produced from a larva, in others asexual, clonal colonies predominate.…”
Section: Bryozoan Growth Forms and Sedimentationmentioning
confidence: 99%